2023
DOI: 10.1002/advs.202307554
|View full text |Cite
|
Sign up to set email alerts
|

Osmolar Modulation Drives Reversible Cell Cycle Exit and Human Pluripotent Cell Differentiation via NF‐κВ and WNT Signaling

Jonathan Sai‐Hong Chui,
Teresa Izuel‐Idoype,
Alessandra Qualizza
et al.

Abstract: Terminally differentiated cells are commonly regarded as the most stable cell state in adult organisms, characterized by growth arrest while fulfilling their specialized functions. A better understanding of the mechanisms involved in promoting cell cycle exit will improve the ability to differentiate pluripotent cells into mature tissues for both pharmacological and therapeutic use. Here, it demonstrates that a hyperosmolar environment enforces a protective p53‐independent quiescent state in immature hepatoma … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 111 publications
0
0
0
Order By: Relevance
“…Medium compositions previously optimized for functionalized hydrogel cultures with similar iPSC-derived liver cells turned out to not have a large impact on maturity of the individual cell types in the spheroid cultures; only the high amino acid and L-Serine concentrations had a significant impact on CYP3A4 levels. Most probably, the hyperosmolar environment created by the L-Serine enforces a protective p53-independent quiescent state in the iPSC-derived hepatocytes, thereby promoting functional maturations (Chui et al 2024). Previous studies have already shown that growth factors can be (partly) replaced by small molecules, leading to successful differentiation of hepatocytes (Siller et al 2015, Pan et al 2022, Vanmarcke et al 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Medium compositions previously optimized for functionalized hydrogel cultures with similar iPSC-derived liver cells turned out to not have a large impact on maturity of the individual cell types in the spheroid cultures; only the high amino acid and L-Serine concentrations had a significant impact on CYP3A4 levels. Most probably, the hyperosmolar environment created by the L-Serine enforces a protective p53-independent quiescent state in the iPSC-derived hepatocytes, thereby promoting functional maturations (Chui et al 2024). Previous studies have already shown that growth factors can be (partly) replaced by small molecules, leading to successful differentiation of hepatocytes (Siller et al 2015, Pan et al 2022, Vanmarcke et al 2023.…”
Section: Discussionmentioning
confidence: 99%